2005
DOI: 10.2960/j.v35.m482
|View full text |Cite
|
Sign up to set email alerts
|

Semi-pelagic Longline and Trammel Net Elasmobranch Catches in Southern Portugal: Catch Composition, Catch Rates and Discards

Abstract: In Portugal, elasmobranch landings have decreased substantially in recent years. In this work, elasmobranch catches in semi-pelagic longlines (1997 and 1998) were compared with those in trammel nets (2000) in the Algarve, southern Portugal areas. In the semi-pelagic longline fishery, 7 elasmobranch species represented 33.4% (2 185 specimens) of the total fish catches. Among the elasmobranch species, the most abundant were Galeus melastomus (63.3%), Etmopterus pusillus (21.7%) and Scyliorhinus canicula (14.2%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 8 publications
2
39
2
1
Order By: Relevance
“…Three of the studied species, E. pusillus, E. spinax, and G. melastomus, are very frequent and are probably the most common elasmobranch species at the depths fished in this study (Monteiro et al, 2001;Coelho et al, 2005), while the fourth species, G. atlanticus, is a relatively rare species, that given its similarity to G. melastomus can easily be confounded. In fact this species has only recently been redescribed based on exterior field marks (Rey et al, 2006) and is still not recognized by the official Portuguese fisheries statistics where it is mixed with G. melastomus.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Three of the studied species, E. pusillus, E. spinax, and G. melastomus, are very frequent and are probably the most common elasmobranch species at the depths fished in this study (Monteiro et al, 2001;Coelho et al, 2005), while the fourth species, G. atlanticus, is a relatively rare species, that given its similarity to G. melastomus can easily be confounded. In fact this species has only recently been redescribed based on exterior field marks (Rey et al, 2006) and is still not recognized by the official Portuguese fisheries statistics where it is mixed with G. melastomus.…”
Section: Discussionmentioning
confidence: 95%
“…Monteiro et al (2001) looked into general discards from the trawl fishery, Erzini et al (2001) studied the hake deep water longline fishery and Coelho et al (2005) analyzed elasmobranch by-catch from coastal trammel nets and semi-pelagic deep water longlines. These studies presented quantitative values of the by-catch in number or biomass, but did not explore intra-specific characteristics of the by-catch such as length distribution, maturity distribution, or sex ratios of the species caught with the different fishing gears.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COELHO et al (2005) reported that catches of elasmobranchs were high in the longline fishery of the coasts of Southern Portugal, owing to setting in deeper waters than the trammel nets. This results from the fact that longlines with baited hooks attract fish from considerable distances (BJORDAL and L KKEBORG, 1996), whereas trammel nets depend on the normal movements of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial catch indicators for the southern North Sea reveal declines already starting in the late 1880s (Lundbeck 1962), and by-catch and mortality analyses show consistently high pressure on elasmo branch populations in the North Sea until the present (Philippart 1998, Piet et al 2009). Causes in clude demersal trawling that equally affects both skates and sharks in shelf sea areas, and longline fisheries in coastal and offshore waters, which pose a further threat to sharks (Stevens et al 2000, Baum et al 2003, Coelho et al 2005.…”
Section: Introductionmentioning
confidence: 99%